2012
DOI: 10.1016/j.crvi.2012.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation du Cd et du Zn chez les plants de tomates (Lycopersicon esculentum L.)

Abstract: Biologie et pathologie ve ´ge ´tales/Plant biology and pathology Bioaccumulation du Cd et du Zn chez les plants de tomates (Lycopersicon esculentum L.) Bioaccumulation of cadmium and zinc in tomato (Lycopersicon esculentum L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 45 publications
0
9
1
Order By: Relevance
“…However, our findings are in contrast to those reported by Sbartai et al, (2012) who showed that exposure of tomato plants to Cd induced a decrease in the content of Chlorophyll a and b, while the low concentration Zn stimulated their biosynthesis. Otherwise, Lei et al, (2012) noted a decline in chlorophyll content after exposure of Seagrass Thalassia hemprichii species to higher Zn and Cd concentrations which could be due to the disruption and damage of chloroplasts and the reduced number of thylakoids as well as the inhibition of nutrient absorption.…”
Section: Discussioncontrasting
confidence: 99%
“…However, our findings are in contrast to those reported by Sbartai et al, (2012) who showed that exposure of tomato plants to Cd induced a decrease in the content of Chlorophyll a and b, while the low concentration Zn stimulated their biosynthesis. Otherwise, Lei et al, (2012) noted a decline in chlorophyll content after exposure of Seagrass Thalassia hemprichii species to higher Zn and Cd concentrations which could be due to the disruption and damage of chloroplasts and the reduced number of thylakoids as well as the inhibition of nutrient absorption.…”
Section: Discussioncontrasting
confidence: 99%
“…These mechanisms include the chelation and sequestration of ions by specific ligands to maintain them at low levels in the cytosol (Sbartai et al, 2012). Chelation of trace elements is a ubiquitous detoxification strategy described in a wide range of plants (Yadav, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Farmers used wastewater in irrigation, because they were rich in nutrients elements [5]. The pollutants located in wastewater can be accumulated in the soil, can be absorbed by plants [6,7], and can be also percolated from groundwater [8]. The toxicity of heavy metals is mainly due to their tendency to accumulate in living organisms and to concentrate along trophic chains [9].…”
Section: Introductionmentioning
confidence: 99%